The privacy of the accused's right to defense between legislative drafting and protected interest: Analytical and comparative study - Zaeem Nasser Hamed Al-Shuaibi (المجلة الدولية للبحوث والدراسات القانونية, 2025)
The right of defense is one of the most elementary ones for all that has a problem in judiciary and is viewed as part of the natural rights which are inextricably connected to numerous constitutional laws forever. The end it prioritizes is justice. To enjoy this right, there are subjective and objective requirements which should exist so that it will be possible for an individual effectively to exercise his right. Right to defense is closely related to several constitutional rights and its fundamental aim is to bring justice to life; to be able to use this right several personal and substantive conditions should be met.The right of defense is subject to personal and objective conditions which are necessary but not sufficient for an accused person to be able to make it actual exercise. This right carries with it the power to defend himself personally from charges against him and that he is the best equipped person to refute charges directed at him.Accordingly, competent authorities have a duty to alert the accused specifically to the charges against him, to afford him full access to the case file and to secure his presence at trial, thus offering him the opportunity to adequately defend himself against all charges.